Tailored surface chemistry of SiO2 particles with improved rheological, thermal-mechanical and adhesive properties of epoxy based composites for underfill applications. (7th November 2018) - Li, Gang; He, Yachuan; Zhu, Pengli; Zhao, Tao; Sun, Rong; Lu, Daniel; Wong, Ching-ping
Abstract: Recently, the silica particles filled epoxy-based composites underfill has gained more and more attentions with the development of flip chip technology towards high density and fine-pitch. However, serious agglomeration and poor dispersion of SiO2 in polymer matrix inevitably leads to deterioration of the rheological and thermal-mechanical properties. The filler surface treatment technology has been well demonstrated to be effective in controlling interfacial compatibility and interfacial interaction of their filled composites and thus enhancing their mechanical properties. However, the role of surface characteristics of SiO2 fillers on the properties associated with underfill such as rheological, coefficient of thermal expansion (CTE) as well as adhesive strength has been rarely reported. In this paper, surface modification of SiO2 particles have been conducted using silane coupling agents with various functional groups. We have attempted to establish a qualitative structure-property relationship between microscopic filler surface chemistry and macroscopic properties of the resulting composites underfill. The results showed that surface modification enabled to decrease underfill viscosity obviously and surface modification with nonpolar groups, such as methacryloxy and phenyl groups showed a much higher efficiency for viscosity reduction than their polar groups counterparts, such as amino and epoxy groups. Meanwhile, underfill with these nonpolar groups modified SiO2 exhibited much higher adhesion strength, accompanied by a conversion of failure mode from the adhesive failure to cohesion failure. In contrast, surface modification with those polar groups was more beneficial to decrease CTE of composites underfill. Our work is believed to be of great value for the design of SiO2 particle-based composites underfill with tailored properties. Graphical abstract: